2021
DOI: 10.1021/acsomega.1c01221
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Charge Approach to Investigating the Influence of Oil Contacting Clay Minerals on Wettability Alteration

Abstract: Reservoir rock wettability has been linked to the adsorption of crude fractions on the rock, with much attention often paid to the bulk mineralogy rather than contacting minerals. Crude oil is contacted by different minerals that contribute to rock wettability. The clay mineral effect on wettability alterations is examined using the mineral surface charge. Also, the pH change effect due to well operations was investigated. Clay mineral surface charge was examined using zeta potential computed from the particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…The positive surface charge can be attributed to the cations present in the system; however, because of the different hydration stabilities of the cations, the observed positive surface charge is due to the Na atom rather than the Mg or Ca atoms, as their hydration stability would not allow them to approach the surface. In addition, the mode of cation interaction with the surface is via adsorption, as earlier reported by Mohammed et al [ 4 ], in the same pH range. In the case of SW, no pH change is observed, with the surface charge of chlorite being negative.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…The positive surface charge can be attributed to the cations present in the system; however, because of the different hydration stabilities of the cations, the observed positive surface charge is due to the Na atom rather than the Mg or Ca atoms, as their hydration stability would not allow them to approach the surface. In addition, the mode of cation interaction with the surface is via adsorption, as earlier reported by Mohammed et al [ 4 ], in the same pH range. In the case of SW, no pH change is observed, with the surface charge of chlorite being negative.…”
Section: Resultssupporting
confidence: 54%
“…The materials used in this study are as reported by Mohammed et al [ 4 ]. Mineral particles used are of average particle size of 11.28, 3.16, 4.57, and 2.64 µm, for chlorite, illite, kaolinite, and montmorillonite, respectively, with all chemicals used of American Chemical Society (ACS) reagent grade.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported water chemistry (i.e. salt composition) can affect the surface charges of clay particles (Kumar et al 2017;Mohammed et al 2021). Unlike settling tests which can take weeks to measure appreciable settling in high clay, dispersed systems, the SRF was able to measure these effects in hours.…”
Section: Preliminary Stage: Srf Testmentioning
confidence: 99%